A New Marine Nematode Species, Metalinhomoeus ramsarensis (Linhomoeidae Filipjev, 1922) from Kuching Wetland National Park, Sarawak, Malaysia - Chen, Cheng Ann; Shabdin Mohd Long (UNIMAS, 2015)
A new marine nematode species from the genus Metalinhomoeus (de Man, 1907) was found in Kuching Wetland National Park (KWNP). The total body size of Metalinhomoeus ramsarensis sp. nov. was extremely long. The head was recorded to be round with four cephalic setae followed by four sub cephalic setae. The inner and outer labial papillae were not clearly observed. An oesophageal bulb was present at the end of the oesophagus. Spicules were known to have central cuticularized strip. Tail of Metalinhomoeus ramsarensis sp. nov. was short and blunt.